Marketing Mix Strategy in Al-Qur'an Perspective - Achmad, Yudianto; Edy, Sarwo (DPPM Universitas Pelita Bangsa, 2023)
The rapid development of sharia-based business in the world and in Indonesia, among others, is shown by the many opportunities open to sharia business, which requires various companies to aggressively develop marketing mix strategies for their products that apply sharia principles. The main basis of sharia principles is based on values or substantive content contained in various surahs and verses of the Qur'an, as well as hadiths, all of which are related to the values of sharia business principles. Meanwhile, the marketing mix theory states that there are 4 variables in marketing, known as the